Hubungan Tingkat Stres, Kualitas Tidur, dan Karakteristik Mahasiswa dengan pH Saliva Mahasiswa/I Fakultas Kedokteran Universitas Prima Indonesia saat Objective Structured Clinical Examination (OSCE) - Beatrice Benedicta Siahaan; Masdalena Nasution; Herlin Novita Pane (Universitas Malahayati, 2026)
ABSTRACT In medical education, the Objective Structured Clinical Examination (OSCE) is extensively used to evaluate students' clinical competencies. Despite its educational value, the examination is frequently identified as a major academic stressor for medical students. Stress and poor sleep quality are known to affect the autonomic nervous system and salivary secretion, potentially altering salivary pH. However, studies integrating psychological factors, sleep quality, student characteristics, and salivary biomarkers remain limited. To determine the relationship between stress levels, sleep quality, and OSCE participants’ characteristics with salivary pH among students of the Faculty of Medicine, Universitas Prima Indonesia. This cross-sectional study used an observational analytical quantitative technique and involved 218 students from Prima Indonesia University's Faculty of Medicine. The respondents were selected using a stratified random sampling technique. The respondents' stress levels were then measured using the Depression Anxiety Stress Scale-21 (DASS-21), their sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI), and the acidity of their saliva was measured using salivary pH indicator paper. Following data analysis using the Spearman, Mann-Whitney, and Kruskal-Wallis tests, the study's statistical significance level was set at a p-value of less than 0.05 (p 0.05). Most respondents had neutral salivary pH (74.8%), poor sleep quality (85.8%), and 59.2% experienced stress ranging from mild to extremely severe levels. “The findings indicated a significant correlation between stress level and salivary pH (r = 0.186; p = 0.006). By contrast, the relationship between sleep quality and salivary pH did not reach statistical significance (r = 0.121; p = 0.074). Similarly, comparisons by sex, age group, and academic semester demonstrated no significant differences in salivary pH (p = 0.498, p = 0.288, and p = 0.126, respectively). Conversely, a significant difference in salivary pH was detected between students with different living arrangements (p = 0.022).”Stress level and living arrangement status were significantly associated with salivary pH among medical students during the OSCE. In contrast, sleep quality, sex, age, and academic semester showed no significant association with salivary pH. Keywords: Academic Stress, Sleep Quality, Salivary pH, OSCE, Medical Students. ABSTRAK Sebagai salah satu bentuk evaluasi kompetensi klinis, Objective Structured Clinical Examination (OSCE) telah menjadi bagian penting dalam proses pendidikan kedokteran. Di sisi lain, berbagai penelitian menunjukkan bahwa pelaksanaan OSCE sering dipersepsikan sebagai salah satu sumber utama stres akademik di kalangan mahasiswa kedokteran. Stres dan kualitas tidur yang buruk diketahui dapat memengaruhi sistem saraf otonom dan sekresi saliva sehingga berpotensi mengubah pH saliva. Namun, penelitian yang mengintegrasikan faktor psikologis, kualitas tidur, karakteristik mahasiswa, dan biomarker saliva masih terbatas. Menganalisis hubungan antara tingkat stres, kualitas tidur, dan karakteristik peserta yang mengikuti Objective Structured Clinical Examination (OSCE). terhadap pH saliva mahasiswa Fakultas Kedokteran Universitas Prima Indonesia. Kajian Ilmiah potong lintang ini menggunakan teknik kuantitatif analitik observasional dan melibatkan 218 mahasiswa dari Fakultas Kedokteran Universitas Prima Indonesia. Responden dipilih menggunakan teknik pengambilan sampel acak bert stratified. Tingkat stres responden kemudian diukur menggunakan Skala Depresi Kecemasan Stres-21 (DASS-21), kualitas tidur mereka diukur menggunakan Indeks Kualitas Tidur Pittsburgh (PSQI), dan keasaman saliva mereka diukur menggunakan kertas indikator pH saliva. Setelah analisis data menggunakan uji Spearman, Mann-Whitney, dan Kruskal-Wallis, tingkat signifikansi statistik penelitian ditetapkan pada nilai p kurang dari 0,05 (p 0,05). Sebagian besar responden memiliki pH saliva netral (74,8%), mengalami kualitas tidur buruk (85,8%), dan 59,2% mengalami stres dari kategori ringan hingga sangat berat. “Terdapat hubungan signifikan antara tingkat stres dan pH saliva (r=0,186; p=0,006). Tidak terdapat hubungan signifikan antara kualitas tidur dan pH saliva (r=0,121; p=0,074). Tidak ditemukan perbedaan pH saliva berdasarkan jenis kelamin (p=0,498), usia (p=0,288), dan semester (p=0,126). Perbedaan signifikan ditemukan berdasarkan status tempat tinggal (p=0,022).” Tingkat stres dan status tempat tinggal memiliki hubungan bermakna terhadap pH saliva mahasiswa saat OSCE. Kualitas tidur, jenis kelamin, usia, dan semester tidak menunjukkan hubungan yang signifikan. Kata Kunci: Stres Akademik, Kualitas Tidur, pH Saliva, OSCE, Mahasiswa Kedokteran.